Power and position: exploring the post-colonial women and men in Jane Eyre and Wide Sargasso Sea - Tabassum, Tasneem (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.